THE RELATIONSHIP OF INTERPERSONAL COMMUNICATION BETWEEN PARENTS OF STUDENTS AND CHILDREN'S COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD EDUCATION (PAUD) PERMATA HATI BUMI AGUNG WAY KANAN - Jupri Jupri; Iis Purnasari (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The problem in this research is the low cognitive development of class A students at PAUD Permata Hati Bumi Agung Way Kanan Regency. Aims to determine the relationship between interpersonal communication between parents and children with the cognitive development of class A students at PAUD Permata Hati Bumi Agung Way Kanan Regency. The research method in this research is correlational with the type of research used, namely quantitative research. The population in this study was 17 students. The sampling technique in this study used the Saturated Sampling Technique, where all the population in this study was sampled. The sample in this study included parents and hildren or in one class or study group, namely 34 people consisting of 17 children and 17 parents. The data collection technique used a questionnaire. The data analysis technique uses product moment correlation. The results of the research show that there is a significant relationship between interpersonal communication between parents and children and the cognitive development of class A children at PAUD Permata Hati Bumi Agung Way Kanan Regency.